Model-based Dynamic Fractional-order Sliding Mode Controller Design for Performance Analysis and Control of a Coupled Tank Liquid-level System - SEKBAN, H. T.; CAN, K.; BASCI, A. (Advances in Electrical and Computer Engineering, 2020)
In this paper, a model-based dynamic fractional-order sliding mode controller (FOSMC) is designed and implemented to a coupled tank experimental setup for controlling the liquid level. First, a model-based dynamic sliding-mode controller is designed by using the dynamic equations of a vertically positioned coupled tank system. Then, the sliding surface of the sliding-mode controller is defined in fractional order so that the designed controller can make better water level tracking. The liquid level control of the system is realized in two different steps. In the first step, the water level of the upper tank is controlled by a pump and in this application the bottom tank is not considered. In the second step, the water level of the bottom tank is controlled with upper tank's output water. In addition, a model-based dynamic sliding mode controller (SMC) is also applied to the system to show the performance of the proposed controller in terms of robustness to disturbances, reference tracking and error elimination capability. Experimental results show that the proposed controller reduces the reference tracking error by 3.68% and 10.17% for the upper tank and 17.07% for the bottom tank when compared to the SMC, and the control signal contains more chattering than the SMC.